Interfacial study of clathrates confined in reversed silica pores - Mileo, Paulo G M; Rogge, Sven M J; Houlleberghs, Maarten; Breynaert, Eric; Martens, Johan A; Van Speybroeck, Veronique (Journal of materials chemistry. A, Materials for energy and sustainability, 2021)
Storing methane in clathrates is one of the most promising alternatives for transporting natural gas (NG) as it offers similar gas densities to liquefied and compressed NG while offering lower safety risks. However, the practical use of clathrates is limited given the extremely low temperatures and high pressures necessary to form these structures. Therefore, it has been suggested to confine clathrates in nanoporous materials, as this can facilitate clathrate's formation conditions while preserving its CH volumetric storage. Yet, the choice of nanoporous materials to be employed as the clathrate growing platform is still rather arbitrary. Herein, we tackle this challenge in a systematic way by computationally exploring the stability of clathrates confined in alkyl-grafted silica materials with different pore sizes, ligand densities and ligand types. Based on our findings, we are able to propose key design criteria for nanoporous materials favoring the stability of a neighbouring clathrate phase, namely large pore sizes, high ligand densities, and smooth pore walls. We hope that the atomistic insight provided in this work will guide and facilitate the development of new nanomaterials designed to promote the formation of clathrates.